5
$\begingroup$

Bibhu said to Bigyata, "I was twice as old as you were when I was as old as you are.". If the sum of their ages is 35 years, find their present ages.

My Attempt:

Let the present ages of Bibhu and Bigyata be $x$ years and $y$ years respectively. From the second statement of the question: $x+y=35$.

$y=35-x$.

But I did not understand the first condition(the first statement) given in the question. Please help.

| cite | improve this question | | | | |
$\endgroup$
  • $\begingroup$ In your attempt: Case 2? Where's case 1? $\endgroup$ – suomynonA Oct 13 '16 at 2:05
  • $\begingroup$ @suomynonA, I have stated that I did not understand the first condition given in the question, which is the case 1. $\endgroup$ – pi-π Oct 13 '16 at 2:08
  • $\begingroup$ That's just confusing...can you clarify in your question by explaining and removing the case 2 part? $\endgroup$ – suomynonA Oct 13 '16 at 2:09
  • $\begingroup$ You mean, $y=35-x$? Where does $50$ comes from? $\endgroup$ – Bhaskar Vashishth Oct 13 '16 at 2:10
  • 1
    $\begingroup$ @user354073 I made an answer; if you need any more clarification just comment. $\endgroup$ – suomynonA Oct 13 '16 at 2:17
1
$\begingroup$

Maybe the problem is easier to comprehend if you consider another variable $$\theta = number\ of\ years\ to\ go\ back\ in\ time\ for\ Bibhu\ to\ be\ twice\ as\ old\ as\ Bigyata$$

We have now 3 equations,

  1. "Bibhu ($x$) was twice as old as Bigyata ($y$) $\theta$ years ago": $$x-\theta=2(y-\theta)$$

  2. "sum of their age is 35": $$x+y=35$$

  3. and we know that $\theta$ years ago Bibhu was Bigyata's age: $$x=y+\theta$$thus $$\theta=x-y$$

Replacing $\theta$ in the equation 1. we get $$x=\frac{3}{2}y$$ replacing $x$ in 2., $y=14$, and $x=21$

| cite | improve this answer | | | | |
$\endgroup$
7
$\begingroup$

Hint:

The equations will be $$x+y=35$$ and $$x-(x-y)=2(y-(x-y))$$ where $x$ is Bibhu's age and $y$ is Bigyata's age.

Here is some explanation for how to get the second equation:

Left hand side of equation: The year when Bibhu was as old as Bigyata would be Bibhu's age minus the difference between the ages.

Right hand side of equation: Since you go back $x-y$ years ago for Bibhu, you also have to do that for Bigyata. You multiply this by 2 because Bibhu says that at that time she was twice as old as Bigyata.

| cite | improve this answer | | | | |
$\endgroup$
6
$\begingroup$

Clearly $x\ge y$.

Second case simplifies to $y=2(y-(x-y))=2(2y-x)=4y-2x$ i.e. $3y=2x$.

Think about it, when Bhibhu was the same age as Bigyata is now i.e. $y$ , (means they are talking about $x-y$ years before), then Bigyata was $y-(x-y)$ years old and twice that is $2(y-(x-y))$.

Therefore, $y=35-\frac{3y}{2}$ or $\frac{5y}{2}=35$.

Thus $y=14$ and $x=21$

| cite | improve this answer | | | | |
$\endgroup$
2
$\begingroup$

$ x + y = 35$ and k years before bhibhu was as old as bhigyata is now. $ x-k =y , x-k = 2 ( y- k)$ solving these equations will give you $ k = 7, x= 21, y=14$

| cite | improve this answer | | | | |
$\endgroup$
0
$\begingroup$

An easier way to think about it is if you take 4 variables, $x_1, x_2, y_1, y_2$ with $x, y$ representing Bigyata and Bhibhu respectively and the index $1, 2$ meaning then and now respectively. With that the first statement becomes:

$(I) 2x_1 = y_1 \land y_1 = x_2$

we also have $(II) x_2 + y_2 = 35$

and $(III)x_2 - x_1 = y_2 - y_1$, i.e. the time difference between then and now

It now become easy to solve for any variable, e.g. for $x_1$ we have from $(II): 35=x_2+y_2=^{(I)}y_1+y_2=^{(III)}x_2-x_1+2y_1=^{(I)}5x_1$

| cite | improve this answer | | | | |
$\endgroup$
0
$\begingroup$

Let their present ages be $x$ & $y$. It is given $x+y=35$--(equation 1) and we have to find out $x$ & $y$. Let the years before from the current year be denoted as $'t'$. $x-t=2(y-t)$ (OR) $x-2y= -t$ --> I was twice as old as you were. (eqn 2) $x-t=y$ (OR) $x-y =t$ --> when I was as old as you are. (eqn 3) From eqns 2 & 3 we can calculate the value of $y$ which is $2t$ (eqn 4) Substitute the value of $2t$ for y in eqn $3$ which gives $x-t=2t$ or $x=3t$ (eqn 5). Sutstitute these $x$ & $y$ values in eqn $1$ which gives $5t=35$ or $t=7.$ From this we can find out the values of x&y using eqns 4&5.So the answer is $21$ & $14$.

| cite | improve this answer | | | | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.